2022
DOI: 10.3390/jcm11123417
|View full text |Cite
|
Sign up to set email alerts
|

The Clinical Relevance of Hypothyroidism in Patients with Solid Non-Thyroid Cancer: A Tantalizing Conundrum

Abstract: Hypothyroidism in patients with solid non-thyroid cancer is a tantalizing entity, integrating an intriguing thyroid hormones (THs)–cancer association with the complexity of hypothyroidism itself. The present narrative review provides a comprehensive overview of the clinical relevance of hypothyroidism in solid non-thyroid cancer. Hypothyroidism in patients with solid non-thyroid cancer is reminiscent of hypothyroidism in the general population, yet also poses distinct challenges due to the dual role of THs in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 150 publications
0
3
0
Order By: Relevance
“…Many patients with a cancer diagnosis present with new or chronic thyroid issues [10,11]. Correspondingly, clinical and sub-clinical hypothyroidism or hyperthyroidism has been implicated in various common cancers including prostate cancer, lung cancer, gastrointestinal cancers, and breast cancer [12][13][14]; however, some of these cases of thyroid malfunction might be incidentally identi ed as thyroid disorders due to a result of their cancer status or treatment [15]. Nevertheless, underestimated hypothyroidism and hyperthyroidism may pose a problem to oncologists treating patients with symptoms related to cancer pathogenesis and treatment, which may result in reducing medication doses unnecessarily or putting treatment temporarily on hold.…”
Section: Introductionmentioning
confidence: 99%
“…Many patients with a cancer diagnosis present with new or chronic thyroid issues [10,11]. Correspondingly, clinical and sub-clinical hypothyroidism or hyperthyroidism has been implicated in various common cancers including prostate cancer, lung cancer, gastrointestinal cancers, and breast cancer [12][13][14]; however, some of these cases of thyroid malfunction might be incidentally identi ed as thyroid disorders due to a result of their cancer status or treatment [15]. Nevertheless, underestimated hypothyroidism and hyperthyroidism may pose a problem to oncologists treating patients with symptoms related to cancer pathogenesis and treatment, which may result in reducing medication doses unnecessarily or putting treatment temporarily on hold.…”
Section: Introductionmentioning
confidence: 99%
“…Our study showed that the change in the level of GnRH in the hypothalamus in rats of the reference groups had no gender specificity: it decreased in the animals of both sexes against the background of hypothyroidism, while it increased during the growth of Guerin's carcinoma. However, it is known that the combination of two pathologies can affect different pathways of regulation that is why the presence of comorbid pathology complicates and modifies the course of the primary disease [19]. In the main group, the gender differences were revealed in the direction of changes in the level of GnRH of the hypothalamus: in the females, induced hypothyroidism inhibited the increase in volumes, and the level of GnRH in the hypothalamus increased, similar to the processes in reference group No.…”
Section: Discussionmentioning
confidence: 99%
“…Many patients with a cancer diagnosis present with new or chronic thyroid issues [10,11]. Correspondingly, clinical and sub-clinical hypothyroidism or hyperthyroidism has been implicated in various common cancers including prostate cancer, lung cancer, gastrointestinal cancers, and breast cancer [12][13][14]; however, some of these cases of thyroid malfunction might be incidentally identi ed as thyroid disorders due to a result of their cancer status or treatment [15]. Nevertheless, underestimated hypothyroidism and hyperthyroidism may pose a problem to oncologists treating patients with symptoms related to cancer pathogenesis and treatment, which may result in reducing medication doses unnecessarily or putting treatment temporarily on hold.…”
Section: Introductionmentioning
confidence: 99%